Uzbek folk traditional instrument - Khodzhieva Zamirahon Kochkarovna (Peerian Journals Publishing, 2022)
A musical instrument is an object that produces musical sounds. Any sound-producing object can be used as a musical instrument. The history of musical instruments dates back to the time when human culture began to take shape. Early musical instruments were used in various rituals, such as during religious events. Later, it was used to play musical instruments.
Keywords: music; rubob; source; note